2007
DOI: 10.1111/j.1432-2277.2007.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-heart beating organ donation: overview and future perspectives

Abstract: Summary New indications for organ transplantation combined with a stagnating number of available donor grafts have severely lengthened the waiting list for almost all types of transplantations. This has led to a renewed interest in non‐heart beating (NHB) donation, as a possible solution to bridge the gap between supply and demand. In this review, we present an overview of current NHB donation practice, outcome, existing problems and future perspectives. We focus on possible improvements in donor management, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 102 publications
1
43
1
2
Order By: Relevance
“…Hypothermic machine perfusion (HMP) preserves kidney grafts by continuous or pulsatile administration of a recirculating cold (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) • C) preservation solution. The Machine Preservation Trial (MP Trial) recently showed that HMP decreases the incidence of primary nonfunction (PNF) and delayed graft function (DGF), and increases 1-year graft survival compared to standard static cold storage (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothermic machine perfusion (HMP) preserves kidney grafts by continuous or pulsatile administration of a recirculating cold (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) • C) preservation solution. The Machine Preservation Trial (MP Trial) recently showed that HMP decreases the incidence of primary nonfunction (PNF) and delayed graft function (DGF), and increases 1-year graft survival compared to standard static cold storage (1).…”
Section: Introductionmentioning
confidence: 99%
“…As these kidneys have a higher incidence of PNF and DGF compared with standard criteria donor (SCD) kidneys (5,6), the need for specific and sensitive surrogates of their quality is becoming even more critical. The absence of prospective analyses of the association between perfusion parameters and kidney transplant outcome, and the increasingly urgent need for valid predictors of graft outcome led us to analyze the association between prospectively collected RR values and kidney graft outcome in a substudy of the MP Trial.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported no difference in transplant outcomes whether the organs were obtained from appropriately selected post-cardiac arrest patients or from other brain-dead donors. [23][24][25] Non-heart-beating organ donation has also been described after failed resuscitation attempts after in-and out-of-hospital cardiac arrest, 26,27 but these have generally been cases in which sustained ROSC was never achieved. The proportion of cardiac arrest patients dying in the critical care unit and who might be suitable non-heartbeating donors has not been documented.…”
Section: Epidemiology Of Post-cardiac Arrest Syndromementioning
confidence: 99%
“…In 1995, at the first international workshop on NHBD in Maastricht, consensus was reached about donor management protocols, and four different categories of NHB donors were defined as the so-called 'Maastricht classification' [148]. Ever since, the practice of NHBD has increasingly become a part of transplant programs worldwide; within Eurotransplant, 6% of all kidney donors in the year 2005 were NHBD [149]. Although there are very few reports indicating that NHBD programs might have only little impact on potential thoracic organ recovery [150], even in thoracic organ transplantation, use of NHBD has become an option and is clinically used in pulmonary transplantation with increasing tendency [151,152].…”
Section: Nonheart-beating Donors (Nhbd)mentioning
confidence: 99%